New ceramic materials from MSWI bottom ash obtained by an innovative microwave-assisted sintering process. Issue 1 (January 2017) - Taurino, R.; Karamanov, A.; Rosa, R.; Karamanova, E.; Barbieri, L.; Atanasova-Vladimirova, S.; Avdeev, G.; Leonelli, C.
Abstract: Preliminary results on the production of new ceramic bricks by an innovative microwave-assisted sintering process employing MSWI bottom ashes are reported. Microwave heating technique was compared with a conventional thermal treatment with the aims to: (1) study the influence of heat treatment method on the crystallization behavior and on the microstructure of obtained samples; (2) define the crystallization evolution in microwave field; (3) gain an insight into the physical properties of the new samples. Higher crystallinity and new crystal phases were observed in the samples prepared by microwave heating, where precipitation of new sodium rich crystal phases was observed, together with quartz and anorthite, formed in the conventionally prepared samples. The possibility to obtain novel bricks with huge waste amount, in a very short thermal cycle and at relatively low temperatures was demonstrated with significant reductions in the energy demand for their production. Finally, the samples obtained by microwave-assisted sintering are characterized by improved mechanical properties.